The unfinished language of the Peruvian peripheral-neighborhood architecture. A contrast between globalization and dwelling - Ríos Vizcarra, Gonzalo (Universidad de Lima. Carrera de Arquitectura, 2019)
Every language, including the architectural one, is created so that a linguistic group is able to share a narrative that structures a type of reality. Taking into consideration the contemporary peripheral-neighborhood architecture in Peru, this paper aims to go deeper into the current space-time coordinates in which creations will be valid, and determine the current scales of values in which dwellers of these neighborhoods prioritize their requirements and turn them into esthetic products. On that basis, more than one attempt to build forms of communication that imbue with the support elements of buildings or that expand in the spaces segregated by these emerging dwellers can be recognized. In the middle of these confrontations, we discover the characteristics of this unfinished architectural language managed from dwelling.